Inovasi Elektronic Stunting Prevention Mobile Education (E-Supreme) untuk Remaja Tahun 2022 - Dwi Maryanti; Trimeilia Suprihatiningsih; Zulfikar Yusya Mubarak (Abdimas Mandalika, 2023)
Abstract:  The stunting prevalence rate in 2021 will be 24.4%. The distribution of stunting events in 2021 and the results of the Indonesian Nutrition Status Study (SSGI) for the January–December 2021 period show that three provinces with a stunting incidence rate of 30–39% are NTT, NTB, and West Sulawesi. Central Java has a stunting distribution of 20–29%. The main problem causing the high rate of stunting in Indonesia is a combination of low awareness of stunting andThe aim is to increase youth's knowledge about stunting. Method: using the Electronic Stunting Prevention Mobile Education Application Innovation (E-Supreme) application. Results: It is known that the average pre-test score is 66, and the average post-test result is 80. The E-Supreme application can be used as an innovative medium to increase stunting knowledge. E-Supreme's innovative media can be downloaded for easy use on Android-based gadgets.Abstrak: Angka prevalensi stunting pada tahun 2021 sebesar 24,4%. Sebaran kejadian stunting tahun 2021, hasil Studi Status Gizi Indonesia (SSGI) periode Januari-Desember 2021 diketahui 3 Propinsi dengan besaran kejadian stunting 30-39% adalah NTT, NTB dan Sulawesi Barat. Jawa Tengah memiliki sebaran stunting sebesar 20-29%. Permasalahan utama yang menyebabkan masih tingginya stunting di Indonesia adalah kombinasi antara rendahnya kesadaran stunting. Tujuan meningkatkan pengetahuan remaja tentang stunting. Metode : menggunakan aplikasi Electronic Stunting Prevention Mobile Education Application Innovation (E-Supreme). Hasil pengabdian bahwa skor rata-rata pre tes adalah 66 dan hasil rata-rata post test didapatkan 80. Aplikasi  E-Supreme  dapat  digunakan  sebagai  media  inovatif  untuk  meningkatkan pengetahuan stunting. Media inovatif E-Supreme dapat diunduh untuk dengan mudah digunakan pada gadget berbasis android 13.